From mechanisms to therapies: the multifaceted roles of guanylate-binding protein 2 in immunity, cancer, and beyond - Cui, Wenqi; Wang, Tianlu; Feng, Juan (Frontiers in Immunology, 2025)
Guanylate-binding protein 2 (GBP2) is an interferon-inducible GTPase that plays a critical role in innate immunity by defending against viral, bacterial, and parasitic infections through mechanisms such as furin inhibition and inflammasome activation. Beyond infectious disease, GBP2 demonstrates a context-dependent dual role in cancer—acting as either a tumor suppressor or an oncogene by modulating key signaling pathways including JAK-STAT, Wnt/β-catenin, and PI3K/AKT/mTOR. Its dysregulation is also increasingly implicated in autoimmune, neurological, and metabolic disorders, underscoring its promising utility as a diagnostic biomarker and therapeutic target. This review systematically synthesizes current knowledge on GBP2’s structural features, biological functions, and functional duality. We further explore the paradoxical nature of its context-dependent roles and propose a unifying hypothesis to explain its dual functions, while outlining translational strategies to leverage GBP2’s potential in biomarker development and targeted therapies.